Photocatalytic Removal of Azo Dye and Anthraquinone DyeUsing TiO2 Immobilised on Ceramic Tiles - P. N. Palanisamy; S. K. Kavitha (E-Journal of Chemistry)
The photocatalytic activity of TiO2 immobilized on different supports; cement and ceramic tile, was studied to decolorize two commercial dyes. The catalyst was immobilised by two different techniques, namely, slurry method on ceramic tile and powder scattering on cement. The degradation of the dyes was carried out using UV and solar irradiation. The comparative efficiency of the catalyst immobilised on two different supports was determined. The photodegradation process was monitored by UV-Vis spectrophotometer. The catalyst immobilised on ceramic tile was found to be better than the catalyst immobilised on cement. Experimental results showed that both illumination and the catalyst were necessary for the degradation of the dyes and UV irradiation is more efficient compared to solar irradiation.